The Influence of Job Involvement, Leader Member Exchange (LMX), and Emotional Intelligence on Employee Performance Through Organizational Commitment at Serambi Indonesia - T. Nasharul Julianda; Hafasnuddin; T. Meldi Kesuma (International Journal of Asian Business and Management, 2024)
A mass media organization's ability to succeed is largely dependent on its workforce. Excessive job targets encourage productivity and follow rules, which can cause feelings to rise and negatively impact performance and relationships among coworkers. Through organizational commitment at the Serambi Indonesia office, the goal of this research is to ascertain the impact of job involvement, LMX (Leader-Member Exchange), and emotional intelligence on staff performance. Questionnaires are used to gather data for this quantitative study design. 62 Serambi Indonesia workers make up the sample. Probability sampling is the sample method employed. Using the SmartPLS application as assistance, data analysis techniques include the outer and inner models. As demonstrated by the findings, job participation significantly and favorably affects organizational commitment and worker performance. Performance and organizational commitment from employees are unaffected by LMX. On organizational commitment, emotional intelligence has a favorable and substantial impact. There is no relationship between emotional intelligence and worker performance. Employee performance is significantly and favorably impacted by organizational commitment. Through organizational commitment, work involvement and emotional intelligence impact performance. Organizational commitment made by LMX has no effect on worker performance